Verbal feedback is the primary mechanism for performance-related review in professional english male soccer: A quantitative exploration - Page, T.; Knowles, Z.; Green, M.; Drust, B.; Andrew, M. (International Journal of Sports Physiology and Performance, 2024)
Purpose: Feedback is information that is provided to aid reflection and learning and enhance future performances. Due to the increased demands of professional soccer and governance around staffing structures, the number of stakeholders delivering and receiving feedback has grown over the past 2 decades. The aim of the present study was to explore the feedback strategies used in professional men`s soccer in England.